Asymmetry of VANGL2 in migrating lymphocytes as a tool to monitor activity of the mammalian WNT/planar cell polarity pathway - Kaucká, Markéta; Petersen, Julian; Janovská, Pavlína; Radaszkiewicz, Tomasz; Smyčková, Lucie; Daulat, Avais M; Borg, Jean-Paul; Schulte, Gunnar; Bryja, Vitezslav (Cell communication and signaling, 2015)
BACKGROUND: The WNT/planar-cell-polarity (PCP) pathway is a key regulator of cell polarity and directional cell movements. Core PCP proteins such as Van Gogh-like2 (VANGL2) are evolutionarily highly conserved; however, the mammalian PCP machinery is still poorly understood mainly due to lack of suitable models and quantitative methodology. WNT/PCP has been implicated in many human diseases with the most distinguished positive role in the metastatic process, which accounts for more than 90% of cancer related deaths, and presents therefore an attractive target for pharmacological interventions. However, cellular assays for the assessment of PCP signaling, which would allow a more detailed mechanistic analysis of PCP function and possibly also high throughput screening for chemical compounds targeting mammalian PCP signaling, are still missing. RESULTS: Here we describe a mammalian cell culture model, which correlates B lymphocyte migration of patient-derived MEC1 cells and asymmetric localization of fluorescently-tagged VANGL2. We show by live cell imaging that PCP proteins are polarized in MEC1 cells and that VANGL2 polarization is controlled by the same mechanism as in tissues i.e. it is dependent on casein kinase 1 activity. In addition, destruction of the actin cytoskeleton leads to migratory arrest and cell rounding while VANGL2-EGFP remains polarized suggesting that active PCP signaling visualized by polarized distribution of VANGL2 is a cause for and not a consequence of the asymmetric shape of a migrating cell. CONCLUSIONS: The presented imaging-based methodology allows overcoming limitations of earlier approaches to study the mammalian WNT/PCP pathway, which required in vivo models and analysis of complex tissues. Our system investigating PCP-like signaling on a single-cell level thus opens new possibilities for screening of compounds, which control asymmetric distribution of proteins in the PCP pathway.
Keywords: pohyb buněk; membránové proteiny; Cell Movement; B-Lymphocytes; B-lymfocyty; Leukemia, Lymphocytic, Chronic, B-Cell; Membrane Proteins; intracelulární signální peptidy a proteiny; Intracellular Signaling Peptides and Proteins; nádorové buněčné linie; lidé; signální dráha Wnt; Cell Polarity; Wnt Signaling Pathway; chronická lymfatická leukemie; Cell Line, Tumor; Humans; polarita buněk